GAYA WACANA MEDIA DALAM KONTRUKSI MEDIA TENTANG PEMBERITAAN ELEKTABILITAS PRESIDEN - Irsyadi, Achmad Naufal (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2019)
This article discusses the news relating to the electability of Indonesian President Joko Widodo in the 2019 Presidential Election published in online media. It aims to reveal the style of discourse in media construction about electability reporting on Joko Widodo in MetrotvNews.com. It employs Critical Discourse Analysis of Fairclough which involves analysis of text dimensions and discourse practice. For uncovering and discovering the style of media discourse, the stylistical theory of Ali Imron Al-Mufruf is used. The source of data is the online media in the form of news that reports about Joko Widodo electability in 2019 presidential election. Data analysis is done by referential method to other related reports at MetrotvNews.com. The result shows the discourse style of parallelism used by metrotvnews.com in reporting the electability of Indonesian President Joko Widodo with different time and word but showing a similarity in discourse.